Implementation of Competence Approach in the Professional Education of Prospective Teachers in the Higher Education Conditions - Stukalenko, Nina M.; Murzina, Saule Ashotovna; Kramarenko, Boris Vasilyevich; Ermekova, ZhÐ°dyra Kerimbaevna; Rakisheva, Gulmira Madievna (International Review of Management and Marketing, 2016)
Current pedagogic science states that the new paradigm of education in XXI century is being developed through the increase of personality culture of a prospective teacher, which has to include a system of knowledge, skills, abilities, as well as cultural and moral values, accumulated by the humankind, which are necessary for the development of a competent personality and its professional maturity. Authors of present article define competence as a way of the existence of knowledge, skills, abilities and education, which facilitates personal self-actualization and placement in the world. Due to these reasons, professional training of the prospective teachers becomes a personality-oriented educational process, i.e. the process, which provides the highest demand for the prospective teacher’s personality potential during the realization of pedagogic tasks. Keywords: professional education, pedagogic education, competence approach in education JEL Classifications: I210, I280, Z180